Răspuns: [tex]\bf \red{ \underline{a = 2}}[/tex]
Explicație pas cu pas:
[tex] \bf 40+90:[9+48:(a+6)]=46[/tex]
[tex] \bf 90:[9+48:(a+6)]=46 - 40[/tex]
[tex] \bf 90:[9+48:(a+6)]=6[/tex]
[tex]\bf 90 = 6 \cdot[9+48:(a+6)][/tex]
[tex]\bf 90 : 6 = [9+48:(a+6)][/tex]
[tex]\bf 15 = [9+48:(a+6)][/tex]
[tex]\bf 15 - 9 = 48:(a+6)[/tex]
[tex]\bf 6 = 48:(a+6)[/tex]
[tex]\bf 6 \cdot (a+6) = 48[/tex]
[tex]\bf (a+6) = 48 : 6[/tex]
[tex]\bf (a+6) = 8[/tex]
[tex]\bf a = 8 - 6[/tex]
[tex]\bf \red{ \underline{a = 2}}[/tex]
==pav38==
Baftă multă !